Using indigenous knowledge to link hyper-temporal land cover mapping with land use in the Venezuelan Amazon: “The Forest Pulse”. - Olivero-Anarte, Jesús; Ferri, Francisco; Acevedo, Pelayo; Lobo, Jorge M.; Fa, Julia E.; Farfán-Aguilar, Miguel Ángel; Romero-Pacheco, David; Real-Giménez, Raimundo (Universidad de Costa Rica, 2016)
Remote sensing and traditional ecological knowledge (TEK) can be combined to advance conservation of remote tropical regions. Integrating TEK into monitoring and management of these areas allows for community participation, as well as for offering novel insights into sustainable resource use. We developed a 250m resolution land-cover map of the Western Guyana Shield (Venezuela) based on remote sensing, and used TEK to validate its relevance for indigenous livelihoods and land uses. We first employed a hyper-temporal remotely sensed vegetation index to derive a land classification system. During a 1 300km, eight day fluvial expedition in roadless areas in the Amazonas State (Venezuela), we visited six indigenous communities who provided geo-referenced data on hunting, fishing and farming activities. We overlaid these TEK data onto the land classification map, to link land classes with indigenous use. We characterized land classes using patterns of greenness temporal change and topo-hydrological information, and proposed 12 land-cover types, grouped into five main landscapes: 1) water bodies; 2) open lands/forest edges; 3) evergreen forests; 4) submontane semideciduous forests, and 5) cloud forests. Each land cover class was identified with a pulsating profile describing temporal changes in greenness, hence we labelled our map as "The Forest Pulse". These greenness profiles showed a slightly increasing trend, for the period 2000 to 2009, in the land classes representing grassland and scrubland, and a slightly decreasing trend in the classes representing forests.Our classification shows potential to assess future effects of CC on landscape. Several classes were significantly connected with agriculture, fishing, overall hunting, and more specifically the hunting of mammals. Our results indicate that TEK-based approaches can validate the livelihood importance of landscapes in high-value conservation areas, aiding natural resource management.
Keywords: Amazonas (Región); Desarrollo sostenible; Naturaleza - Conservación - Amazonas; Amazonia; Forest conservation; Greenness; Indigenous people; Land cover; Land use; Remote sensing